2007
DOI: 10.1007/s10750-006-0351-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterioplankton communities of Crater Lake, OR: dynamic changes with euphotic zone food web structure and stable deep water populations

Abstract: The distribution of bacterial and archaeal species in Crater Lake plankton varies dramatically over depth and with time, as assessed by hybridization of group-specific oligonucleotides to RNA extracted from lakewater. Nonmetric, multidimensional scaling (MDS) analysis of relative bacterial phylotype densities revealed complex relationships among assemblages sampled from depth profiles in July, August and September of 1997 through 1999. CL500-11 green nonsulfur bacteria (Phylum Chloroflexi) and marine Group I c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 64 publications
(65 reference statements)
3
24
0
Order By: Relevance
“…The peak relative abundance of CL500-11 in Lake Michigan was similar to that in Lake Biwa, where the same CARD-FISH probe used in the present study was used, while it remained well below the 50% reported in Crater Lake (15,16). Total bacterial and CL500-11 cell numbers were about 1 order of magnitude lower in Lake Michigan than in Lake Biwa, most likely reflecting the lower levels of DOC and nutrients in Lake Michigan, which is oligotrophic (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The peak relative abundance of CL500-11 in Lake Michigan was similar to that in Lake Biwa, where the same CARD-FISH probe used in the present study was used, while it remained well below the 50% reported in Crater Lake (15,16). Total bacterial and CL500-11 cell numbers were about 1 order of magnitude lower in Lake Michigan than in Lake Biwa, most likely reflecting the lower levels of DOC and nutrients in Lake Michigan, which is oligotrophic (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Chloroflexi are rarely observed in freshwater pelagic zones when oxygen is plentiful (8), but CL500-11-like populations are a notable exception and are emerging as a taxon restricted to lakes that are deep enough to maintain low temperatures (Ͻ10°C) in the hypolimnion after stratification (14). This group was first observed in Crater Lake, OR, where it is abundant throughout the year, contributing up to 50% of all cells in the deep (15,16). Since its initial discovery, a similar predominance has been observed in deep lakes around the world, including in Western Europe, East Asia, and, most recently, two of the largest freshwater lakes in the world, Lake Superior and Lake Huron (14,17).…”
mentioning
confidence: 99%
“…Although obtained by a different methodological approach, archaeal abundance in neighboring Lake Victoria reached 5.9% of the total nucleic acids (38). Similar values (between 1 and 7% of DAPI-stained cells) were obtained by FISH and CARD-FISH in different freshwater lakes (36,59), although recent studies carried out in high mountain lakes reported abundances of up to 22% in Crater Lake (87) and 37% in Lake Llebreta (4). In stratified marine environments such as the Cariaco Basin and the Black Sea, the archaeal planktonic fraction ranged from 1% to 9% and from 10% to 30% of total DAPI counts, respectively, showing maximal abundances at the redoxcline coinciding with depth maxima of nitrite and nitrate (15,41,44).…”
Section: Discussionmentioning
confidence: 68%
“…The small contribution of archaea to the planktonic microbial community is a common trait for freshwater environments (Casamayor and Borrego 2009 ) . In this regard, values below 10% of total prokaryotes have usually been reported for different freshwater lakes (Pernthaler et al 1998 ;Jürgens et al 2000 ;Llirós et al 2011 ) , although higher archaeal abundances have been reported (>20% of total cells) in some oligotrophic (Urbach et al 2007 ;Auguet and Casamayor 2008 ) or oligomesotrophic (Callieri et al 2009 ) freshwater lakes.…”
Section: Archaeal and Bacterial Assemblagesmentioning
confidence: 94%